Factors That May Affect Rating and Liking Scores of Septorhinoplasty Videos on YouTube - ŞAHİN, AKIN (SPRINGER, 2020)
Background Despite the increasing use of videos on social media platforms such as YouTube that inform patients about conditions and procedures, it is an enigma how patients benefit from these videos. Although professional healthcare providers play an important role in this regard, there are no data on video characteristics that make a video useful, or likable by the audience. We aimed to investigate that factors make a septorhinoplasty video posted on YouTube successful. Materials and Methods Video demographics, including type, source, length, and viewers' comments, were evaluated. Three researchers independently assessed videos on septorhinoplasty for attractiveness. Nine criteria, including preoperative nasal congestion, snoring, nasal deformity (visuality), surgical treatment, postoperative nasal congestion, bruising\swelling, pain, patient satisfaction, and medical treatment, were examined. Results The number of likes for the videos with preoperative nasal deformity data (visuality) was found to be significantly higher than that for the videos without preoperative nasal deformity (visuality) data. For the videos with surgical treatment data, the number of likes, the number of dislikes, the number of comments, and the total number of views were found to be significantly higher than those for the videos without surgical treatment data (pvalues 0.007, 0.016, 0.006, and 0.003 respectively). Videos with medical treatment data had a significantly higher number of comments than those without medical treatment data. Conclusion The attractiveness of a video on septorhinoplasty increases when it contain both medical and surgical treatment data.
Keywords: YouTube; Septorhinoplasty; Attractiveness score; Video; SOCIAL MEDIA